Analytical model for seismic simulation of reinforced concrete coupled shear walls. (1st August 2018) - Ding, Ran; Tao, Mu-Xuan; Nie, Xin; Mo, Y.L.
Highlights: An efficient, accurate and practical model for RC coupled walls is proposed. The model is adequately validated by eight large-scale test specimens. The interaction between coupling beams and wall piers is thoroughly investigated. The influences of various beam parameters are quantitatively evaluated. Modeling recommendations are provided for RC coupled wall systems. Abstract: Reinforced concrete coupled walls are widely used as the main seismic resistant structural system in high-rise buildings. This paper proposes a new mixed beam-shell model for the seismic analysis of reinforced concrete coupled walls with sufficient efficiency and accuracy on the platform of general finite element software MSC.Marc. Boundary elements at the ends of wall piers are simulated by conventional fiber beam-column elements, while the web of the wall pier is modeled by the layered shell element. Coupling beams are simulated by non-conventional fiber beam-column elements, which can not only take into account the shear and shear-sliding deformation together with various failure modes of conventionally reinforced beams, but also the shear and rebar slip deformation of diagonally reinforced beams. RBE2 link elements are utilized to connect the coupling beams to the wall piers. Eight test specimens reported in the literature are used to validate the proposed model. The mechanism of the coupled wall is thoroughly investigated in terms of the beam deformation, base shear and moment distribution as well as axial force of the wall piers. Furthermore, parametric analyses on specimens with different degrees of coupling and types of reinforcement layouts of coupling beams are conducted. Based on the analyses, the influences of the complex behavior and various modeling parameters of coupling beams on the behavior of coupled wall are revealed quantitatively. As a conclusion of the parametric analyses results, it is recommended that the complicated behavior of coupling beams be accurately considered for most cases in the seismic analysis of coupled wall systems.